Percentage change of FSH value: new variable to predict the seminal outcome after varicocelectomy. (3rd April 2014) - Cantoro, U.; Catanzariti, F.; Lacetera, V.; Quaresima, L.; Giovanni, M.; Polito, M.
Summary In the literature, there is no good agreement with variables to predict seminal outcome after varicocelectomy. The purpose of this study was to evaluate the FSH percentage change (Δ% FSH) as a predictor of the seminal outcome after varicocelectomy together with other known predictors. We evaluated 118 patients who underwent varicocelectomy. We assessed factors that could be predictors of the improvement of semen characteristics: LH, FSH, total and free testosterone before operation, testis volume, age, testicular pain, body mass index (BMI), Δ% FSH, varicocele Doppler ultrasound grade using regression analysis. Mean sperm concentration increased from 27 ± 12 to 52 ± 15 million per ml post‐operatively (P < 0.003), mean sperm motility increased from 31 ± 12 to 40 ± 13 million per ml following the operation (P < 0.02), also mean FSH value changed from 10.2 ± 8.3 to 6.7 ± 7.2 UI/L (P < 0.01). In unvaried regression analysis, Δ% FSH, BMI and age were predictors of the improvement of semen characteristics. In multiple regression analysis, only Δ% FSH and age were predictors. Negative correlation with age and positive correlation with Δ% FSH were observed. Our findings suggest that Δ% FSH (before and after varicocelectomy) and age are significant factors predicting the improvement of semen characteristics.